The effect of working time reduction on short-time compensation: a French empirical analysis - Calavrezo, Oana; Duhautois, Richard; Walkowiak, Emanuelle (Noisy-le-Grand, 2007)
"The short-time compensation (STC) program aims to avoid lay-offs in case of short-term downturns. According to insurance models, STC is an instrument of both job security and flexibility. This paper investigates the impact of workweek reduction to 35 hours on the French STC recourse. We quantify the average decrease in the STC authorized days with kernel matching estimators assessed on a balanced panel of French establishments. We highlight a substitution effect between STC and working time reduction (WTR) due to their internal flexibility role. As a consequence, the WTR policy refocused STC on its initial job security function."